Relationship between phenolic glycolipid antigen (PGL-I) and leprosy detection (Research, Society and Development, 2023)
Understand the advantages and disadvantages of the phenolic glycolipid antigen in the early detection of leprosy. This research consists of an integrative review of the literature, for the search the guiding question was elaborated using the necessary subsidies to enable the location of the studies available in the databases: “What is the relationship between the phenolic glycolipid antigen and the aid in the diagnosis of leprosy ?”. The databases used were: National Library of Medicine National Institutes of Health (PubMed), Science Direct and Virtual Health Library (BVS/MEDLINE). The descriptors and keywords were obtained by consulting the Health Sciences Descriptors (DECS) and Medical Subject Headings (MeSH), the descriptors were “phenolic glycolipid I”, “leprosy”, “diagnosis”, “leprosy” and “diagnosis”. ”. The study had a sample of 8 articles, among which negative and positive aspects of the phenolic glycolipid antigen for the detection of leprosy were discussed. Among them, it was positively listed that the antigen helps to indicate the early diagnosis of the disease, indicates its potential to develop more severe reactions, as well as helps the diagnosis and predicts relapses, while the negative points listed were the low ability to detect true positives, diagnostic insufficiency and impossibility of initiating therapy due to indicating only previous infection. It is clear that more studies are needed on the functionality of the phenolic glycolipid antigen (PGL-I) in the early detection of leprosy, due to the high dichotomy between negative and positive aspects.